RhoA: a dubious molecule in cardiac pathophysiology - Kilian, Lucia Sophie; Voran, Jakob; Frank, Derk; Rangrez, Ashraf Yusuf (Journal of biomedical science, 2021)
The Ras homolog gene family member A (RhoA) is the founding member of Rho GTPase superfamily originally studied in cancer cells where it was found to stimulate cell cycle progression and migration. RhoA acts as a master switch control of actin dynamics essential for maintaining cytoarchitecture of a cell. In the last two decades, however, RhoA has been coined and increasingly investigated as an essential molecule involved in signal transduction and regulation of gene transcription thereby affecting physiological functions such as cell division, survival, proliferation and migration. RhoA has been shown to play an important role in cardiac remodeling and cardiomyopathies; underlying mechanisms are however still poorly understood since the results derived from in vitro and in vivo experiments are still inconclusive. Interestingly its role in the development of cardiomyopathies or heart failure remains largely unclear due to anomalies in the current data available that indicate both cardioprotective and deleterious effects. In this review, we aimed to outline the molecular mechanisms of RhoA activation, to give an overview of its regulators, and the probable mechanisms of signal transduction leading to RhoA activation and induction of downstream effector pathways and corresponding cellular responses in cardiac (patho)physiology. Furthermore, we discuss the existing studies assessing the presented results and shedding light on the often-ambiguous data. Overall, we provide an update of the molecular, physiological and pathological functions of RhoA in the heart and its potential in cardiac therapeutics.